CLIL (CONTENT AND LANGUAGE INTEGRATED LEARNING) FOR ACHIEVING POSITIVE OUTCOMES OF STUDENTS COLLEGE OF ENGLISH PROGRAM - Khulaifiyah, Khulaifiyah (Universitas Negeri Surabaya, 2015)
CLIL is a methodological approach particularly suitable for contexts where students learn content through supplementary teaching materials. The goal of the study is know the positive outcome of Students College after and during the CLIL applied on skill subjects. The sample of this research was semester six students of Islamic University of Riau who were taking Microteaching and ESP subject. Clustering random sampling was used here. The design of the research was an experiment research focus on Post equivalent research. The instruments were questionnaires, and observation. The treatment was given for 8 meetings in form of the students? assignment in giving motivation (story, Al-Quran verse, wise words) for about 5 to 7 minutes. Based on the result, the data showed that there is significant effect of CLIL on the students? outcome of these subjects. The effect of CLIL was the students were stimulated to hear other motivation activities; the students were familiar with the moral values which affected their life style, mind set and behavior. The conclusion was CLIL stimulate students? Perception, Moral Perception, spiritual Perception and appear Positive Habits.